Usulan peningkatan kecepatan produksi di UKM Cokelat Ibunmanis menggunakan soft system methodology - Iphov Kumala Sriwana; Muhammad Almaududi Pulungan; Annisa A. Lestari; Siwi Lintang Pertiwi (AGROINTEK, 2025)
Indonesia is the world's third largest cocoa producer, leading to the high potential for cocoa processing and conversion to downstream industries. However, the downstream production of cocoa processing only reaches low utilization, around 40%. This problem also happens to UKM Ibunmanis in Bandung, which often fails to meet consumer demand. We have done a study to overcome this problem, aiming to make suggestions to improve production process technology,  to increase production capacity and ability to meet consumer demand. Here, we used Soft System Methodology (SSM) to provide solutions to the problems. The SSM consists of seven stages: Problem identification, Rich Picture Diagram, Root Cause Analysis coupled with CATWOE analysis, conceptual model activities (9 model activities), debating, improvement suggestions, and implementation. The results indicate that the transformation process carried out is in the form of processing chocolate bars into downstream products, with the limitation being conventional technology, which has model activities for designing appropriate technology for critical processing processes in UKM. Implementing the appropriate technology can speed up the production process from 30 minutes to 7 minutes or increase process efficiency by 77%. In addition, suggestions resulting from the method for the melting process can gain more profits and increase the sustainability of the SMEs